Model pembelajaran picture-word inductive untuk meningkatkan keterampilan membaca permulaan peserta didik kelas I sekolah dasar - Nurul Aisya Risyam; Sukarno Sukarno; Chumdari Chumdari (Didaktika Dwija Indria, 2021)
The research carried out to improve the early reading skills of A-first-grade at Dukuhan Kerten Surakarta Public Elementary School 2019/2020 academic year. The alternative solution chosen for used of the Picture-Word Inductive Learning Model. This research was structured using a qualitative approach with type of Classroom Action Research. The subjects were 12 A-first-grade students of Dukuhan Kerten Surakarta Public Elementary School. The procedure consisted of two cycles, each cycle consisting of four stages, namely planning, implementing, observing, and reflecting. Data collection was carried out using interview techniques, observation, and documentation study. The validity of the data used was the triangulation of data sources. Data analysis used interactive model of Miles and Huberman's analysis. The results of pre-reading skills always increase until the second cycle and stopped because it had reached the research work indicators. The results of the pre-action had value 53.58 (16.67%) increased in the first cycle to 60.00 (41,67%), increased in the second cycle with a value of 80.00 (83.33%). Thus, it conclusion that  used of the Picture-Word Inductive Learning Model can improve the initial reading skills of A-first-grade at  Dukuhan Kerten Surakarta Public Elementary School for 2019/2020 academic year.